Environmental Cues Modulate Microglial Cell Behavior Upon Shiga Toxin 2 From Enterohemorrhagic Escherichia coli Exposure - Berdasco, Clara; Duhalde Vega, Maite; Rosato-Siri, María Victoria; Goldstein, Jorge (Frontiers in Cellular and Infection Microbiology, 2020)
Shiga toxin (Stx) produced by enterohemorrhagic E. coli produces hemolytic uremic syndrome and encephalopathies in patients, which can lead to either reversible or permanent neurological abnormalities, or even fatal cases depending on the degree of intoxication. It has been observed that the inflammatory component plays a decisive role in the severity of the disease. Therefore, the objective of this work was to evaluate the behavior of microglial cell primary cultures upon Stx2 exposure and heat shock or lipopolysaccharide challenges, as cues which modulate cellular environments, mimicking fever and inflammation states, respectively. In these contexts, activated microglial cells incorporated Stx2, increased their metabolism, phagocytic capacity and pro-inflammatory profile. Stx2uptake was associated to receptor globotriaosylceramide (Gb3)-pathway. Gb3 had three clearly distinguishable distribution patterns which varied according to different contexts. In addition, toxin uptake exhibited both a Gb3-dependent and a Gb3-independent binding depending on those contexts. Altogether, these results suggest a fundamental role for microglial cells in pro-inflammatory processes in encephalopathies due to Stx2 intoxication and highlight the impact of environmental cues.